2022
DOI: 10.3390/microorganisms10040675
|View full text |Cite
|
Sign up to set email alerts
|

Customized Minimally Invasive Protocols for the Clinical and Microbiological Management of the Oral Microbiota

Abstract: In recent years, the personalization of periodontal clinical practice has led to the study of protocols with a proactive approach [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…These observational data provide strong evidence of the role of diet quality in clinical periodontitis and potentially an increased emphasis on addressing these deficiencies in routine dental care. Furthermore, our findings add to the body of literature showing several other emerging therapies, such as using ozonated compounds in gel may reduce periodontitis in diabetes patients [33].…”
Section: Discussionsupporting
confidence: 64%
“…These observational data provide strong evidence of the role of diet quality in clinical periodontitis and potentially an increased emphasis on addressing these deficiencies in routine dental care. Furthermore, our findings add to the body of literature showing several other emerging therapies, such as using ozonated compounds in gel may reduce periodontitis in diabetes patients [33].…”
Section: Discussionsupporting
confidence: 64%
“…Para probiotics are inactivated microbial cells that offer health benefits without posing health risks. They can regulate the immune system, combat pathogens, and exhibit anti-inflammatory, antiproliferative, and antioxidant properties [19,41]. Furthermore, future studies could delve deeper into the specific mechanisms underlying the beneficial effects of probiotics and para probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a shift toward minimally invasive protocols for maintaining a balanced oral microbiota. These protocols include the use of probiotics and Para probiotics to rebalance oral flora, glycine and erythritol-based powders to target specific bacteria, and ozone therapy for its antibacterial and healing properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed the impact of oral microbiome on oral and systemic health, and explored its role in disease diagnosis and treatment. For example, some personalized treatments taking into account the systemic risk of the patients has provided new therapeutic strategies in periodontal and caries pathologies preventions, using new professional protocol or domiciliary use of probiotics [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%